Kultura organizacyjna w wybranych instytucjach oświatowych w Rzeszowie. Analiza socjologiczna - Kinal, Mariola (Uniwersytet Rzeszowski, 2019)
Celem rozprawy doktorskiej jest analiza kultury organizacyjnej wybranych instytucji oświatowych w Rzeszowie. Badaniem objęto trzydzieści wybranych przedszkoli i szkół podstawowych w Rzeszowie. Wzięło w nim udział 19 dyrektorów oraz 486 nauczycieli. Sformułowano cztery problemy badawcze: (1) jaka jest kultura organizacyjna w przebadanych instytucjach oświatowych? (2) jaki styl przywództwa występuje w przebadanych instytucjach oświatowych? (3) Jaka jest komunikacja w przebadanych instytucjach oświatowych? (4) Jakie wartości i normy dominują w przebadanych instytucjach oświatowych? W trakcie analizy zagregowanego materiału badawczego wzięto pod uwagę trzy zmienne: stanowisko zajmowane przez ankietowanego, szczebel edukacyjny oraz typ ustrojowy instytucji oświatowej. Diagnozy kultury organizacyjnej dokonano za pomocą kwestionariusza skierowanego do nauczycieli, wywiadu skategoryzowanego z dyrektorami instytucji oraz kwestionariusza OCAI. Praca doktorska składa się ze wstępu, dwunastu rozdziałów obejmujących teoretyczną warstwę zagadnienia, jednego rozdziału dotyczącego założeń metodologicznych, czterech rozdziałów zawierających odpowiedź na postawione pytania badawcze oraz zakończenia, w którym podsumowano problemy badawcze.

The aim of the doctoral dissertation is to analyze the organizational culture of selected educational institutions in Rzeszow. The study covered thirty selected nursery schools and primary schools in Rzeszow. Nineteen directors and 486 teachers took part in it. Four research problems were formulated: (1) what is the organizational culture in the researched educational institutions? (2) what leadership style occurs in the researched educational institutions? (3) What is the communication in the researched educational institutions? (4) What values and norms dominate in the researched educational institutions? During the analysis of the aggregated research material, three research variables were considered: the position occupied by the surveyed, the educational level and the constitutional type of the educational institution. The diagnosis of organizational culture was made using a questionnaire addressed to teachers, an interview categorized with the directors of the institution and the OCAI questionnaire. The PhD disertation consists of an introduction, twelve chapters covering the theoretical layer of the issue, one chapter on methodological assumptions, four chapters containing the answer to the research questions posed and conclusions, in which the research problems were summarized.
Diagnosing the organizational culture in selected educational institution in Rzeszow. Sociological analysis
Promotor: dr hab. Zbigniew Rykiel, prof. UR - 322 s.
Keywords: kultura organizacyjna; instytucja oświatowa; socjologia edukacji; Rzeszów; organizational culture; educational institution; sociology of education; Rzeszow